Leadership strategies for enhancing border security in Papua: A collaborative approach to surveillance and threat management - Harefa, ​ Faonaso; Supriyadi, Asep Adang (Journal of National Paradigm-Based Resilience Strategy, 2025)
Background: The Papua border region faces significant security challenges due to its remote geography, limited infrastructure, and sparse monitoring resources. These issues hinder swift responses to threats, leaving the border vulnerable to criminal and smuggling activities. Effective leadership strategies that account for local wisdom and foster cross-stakeholder collaboration are essential to address these challenges. Methods: This study uses a qualitative literature review method to synthesize data from relevant studies, government reports, and security assessments. In addition to a primary analysis of previous literature, insights were gathered through the qualitative approach, including interviews and observations conducted over five years. Data collection involved triangulation through interviews with key informants and document analysis, with purposive and snowball sampling to ensure a comprehensive understanding. Findings: Findings indicate that a dual leadership style and collective decision-making approach significantly enhance border security. Engaging local stakeholders, particularly through partnerships with the Indonesian National Armed Forces (TNI), police, and the National Border Management Agency (BNPP), creates an adaptive, sustainable security system. Infrastructure development, informed by local customs and practices, also empowers communities to participate in border monitoring. Conclusion: The combination of flexible, adaptive leadership with a collaborative strategy among central and local entities strengthens border security management in Papua. Emphasizing local participation and infrastructure improvements aligns security efforts with community needs, promoting a more integrated and responsive approach. Novelty/Originality of this article: This study highlights the importance of incorporating local cultural wisdom and multi-stakeholder collaboration in security strategies for the Papua border region. The dual leadership model, combining central and local authorities, along with active community involvement, creates a unique framework for addressing security challenges in remote and resource-limited areas.